Phytase-active lactic acid bacteria from sourdoughs: Isolation and identification. Issue 1 (September 2015) - Nuobariene, Lina; Cizeikiene, Dalia; Gradzeviciute, Egle; Hansen, Åse S.; Rasmussen, Søren K.; Juodeikiene, Grazina; Vogensen, Finn K.
Abstract Whole-grain foods play an important role in human diet as they are relatively rich in minerals, however, the absorption of those minerals in human gut can be very low due to high content of the mineral binding phytate. Therefore, the object of this study was to identify phytase-active lactic acid bacteria (LAB) which could be used as a starter to increase mineral bioavailability in whole-meal bread. Hence, LAB isolates were isolated from Lithuanian sourdoughs, tested for phytase activity, and phytase active isolates were identified. Studies of phytase activity of the isolates were carried out at conditions optimal for leavening of bread dough (pH 5.5 and 30 °C). The phytase active isolates belonged to the species Lactobacillus panis, Lactobacillus reuteri, Lactobacillus fermentum, and Pediococcus pentosaceus. Phytase activities of the tested LAB isolates were both extra- and intra-cellular. The highest extracellular phytase production was found in L. panis with a volumetric phytase activity of 140 U/mL. Phytate degradation in whole-wheat dough fermented with L. panis or L. fermentum was 90% and 70%, respectively.